PENGARUH KINERJA KEPALA SEKOLAH SEBAGAI SUPERVISOR TERHADAP PROFESIONALISME GURU - Lisda Hasrul; Munir Yusuf; Sumardin Raupu (Institut Agama Islam Negeri (IAIN) Palopo, 2021)
This study aims: to determine the performance of the principal as a supervisor at SMP Negeri 1 Palopo; to find out the professionalism of teachers in SMP Negeri 1 Palopo; to determine the effect of the principal’s performance as a supervisor on teacher professionalism at SMP Negeri 1 Palopo. This study use quantitative research methods with ex-post facto research design. The total population is all teachers of SMP Negeri 1 Palopo consisting of 52 civil cervant or honorary teachers with sampling using a saturated sampling technique, namely determining the sample when all members of the population are used the sample. So, the sample used was 52 people. The research instrument use a questionnaire and documentation. Based on the results of the analysis, the principal’s performance as a supervisor at SMP Negeri 1 Palopo was in the good category with a percentage of 56%. Meanwhile, the professionalism of teachers at SMP Negeri 1 Palopo is in the very good category with a percentage of 77%. In addition, it is obtained that T count is 6,884 > T table 1, 675 so it can be concluded that X has an effect on Y with R2 (R square) of 0,487 or 48,7% has a positive and significaneffect of the principal’s performance as a supervisor on teacher professionalism at SMP Negeri 1 Palopo while the rest 51,3% is influenced by other variables that cannot be explained in this study.